1995
DOI: 10.1002/ijc.2910610105
|View full text |Cite
|
Sign up to set email alerts
|

Human T‐Cell lymphotropic virus type I and severe neoplasia of the cervix in jamaica

Abstract: Human T-cell lymphotropic virus type I (HTLV-I) was associated with carcinoma of the cervix in Japan in a recent study that compared hospital cases with healthy population-based controls. To test this relationship in women more alike for cervical neoplasia risk factors (including sexual behavior and human papilloma virus; HPV), we enrolled consecutive patients from a colposcopy clinic in Kingston, Jamaica (an HTLV-I endemic area). Patients underwent Pap smear, colposcopy, biopsy and cervical swab for detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…This is likely to be an HPV-dependent mechanism, where declining immunity is associated with increased HPV DNA proliferation, resulting in an increased risk of HPV-related cancers. There is evidence that immunosuppressive conditions such as diabetes, infection with HIV, or HTLV-1 increase the risk of lower genital tract neoplasia [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to be an HPV-dependent mechanism, where declining immunity is associated with increased HPV DNA proliferation, resulting in an increased risk of HPV-related cancers. There is evidence that immunosuppressive conditions such as diabetes, infection with HIV, or HTLV-1 increase the risk of lower genital tract neoplasia [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…1 Since the majority of cervical lesions regress to normal cytology after a period of 12 months from presumed first infection, it is thought that the remaining cervical lesions persist due to environmental, host and viral cofactors that have a pleiotropic effect on HPV viral replication, the immune system and tissue microenvironment. [2][3][4][5][6][7][8][9][10] Recent studies suggest that HPV16 viral load may be a possible molecular biomarker in the natural history of HPV infection. Using a semi-quantitative measure of HPV16 DNA levels, several observational studies have found a high correlation between high viral load and high-grade intra-epithelial lesions.…”
mentioning
confidence: 99%
“…In Japan, a cross-sectional study 22 observed higher prevalence of HTLV-1 infection in patients with cervical cancer, assigning a threefold higher risk for this malignancy. In Jamaica, a case-control study suggested that HTLV-1 infection was a risk factor for progression of cervical intraepithelial neoplasia 23 . However, another study performed in that same area did not confirm this association 24 .…”
Section: Discussionmentioning
confidence: 99%
“…infection among HTLV-infected and uninfected groups when women were stratified into age ranges (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), 36-45, 46-55, and 56-65 years). Four positive cases of HPV infection (18.2%) were observed in HTLV-infected women with 46-55 years, whereas none was found in the control group at same age (p = 0.31) (data not shown).…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation